Sustaining Urban Growth on an Enhancement of Road Safety - Narinsilp, Sirinthorn; Iamtrakul, Pawinee; Jantaworn, Pornchai (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Urban growth has resulted in many negative problems in Thailand, especially with regards to road safety. The total value of damage came to approximately 116,000 million baht in 2007, meaning that a safety mitigation plan is urgently required to alleviate the problem. Road accidents are a consequence primarily of urban growth and road safety factors - both elements that can be controlled and manipulated. This paper aimed to study the impact of these factors on the behavior and attitudes of road users and the resulting effect on the risk of accidents. Thus, the complex variables were evaluated by Severity Index (SI) to explain the situation of road hazards. Also, the risk area was then identified based on spatial analysis and demonstrated by GIS, using Bangkok-yai District as the study area. The results of the analysis indicated that road safety factors played a role as the most important determinant (0.45), followed by urban physical aspects (0.38) and road characteristics (0.20). This analysis technique could therefore be used to identify the potential area of road traffic accidents, consistent with the risk area identified by users. Finally, with a more precise geographical approach, the potential for traffic crashes in urban areas could be identified and practically applied by city planners, traffic safety engineers and concerned authorities to alleviate or improve road safety standards.